Antiradical and xanthine oxidase inhibitory activity evaluations of Averrhoa bilimbi L. leaves and identification of bioactive constituents through LC-QTOF-MS/MS and molecular docking approach - Ahmed, Qamar Uddin; Alhassan, Alhassan Muhammad; Khatib, Alfi; Shah, Syed Adnan Ali; Hasan, Muhammad Mahmudul; Sarian, Murni Nazira (MDPI, 2018)
The objective of the present study was to investigate the antiradical and xanthine oxidase inhibitory effects of Averrhoa bilimbi leaves. Hence, crude methanolic leaves extract and its resultant fractions namely hexane, chloroform and n-butanol fractions were evaluated for DPPH radical scavenging effect and xanthine oxidase inhibitory activity. The active constituents were tentatively identified through LC-QTOF-MS/MS and molecular docking approaches. The n-butanol fraction of A. bilimbi crude methanolic leaves extract displayed significant DPPH radical scavenging effect with IC50 (4.14 ± 0.21 μg/mL) (p<0.05) as well as xanthine oxidase inhibitory activity with IC50 (64.84 ± 3.93 μg/mL) (p<0.05). Afzelechin 3-O-alpha-L-rhamnopyranoside and cucumerin A were tentatively identified as possible metabolites that contribute to the antioxidant activity of the n-butanol fraction.